The influence of freshwater from terrestrial sources on the concentrations of iron in Kesennuma Bay, Japan, after the 2011 tsunami. (5th February 2020) - Yamamoto, Mitsuo; Liu, Dan; Fukushima, Keitaro; Yokoyama, Katsuhide
Abstract: The earthquake and tsunami that took place off the Pacific Coast of Tohoku, Japan, in 2011 caused serious damage to the coastal areas of the Tohoku and Kanto regions. Samples have been collected either monthly or bi-monthly since the tsunami to facilitate an investigation of how the coastal environment in Kesennuma Bay, Miyagi Prefecture, northeastern Japan, was affected by the tsunami. In this study, information about iron (Fe), nitrogen (N), and phosphorus (P) concentrations, and salinity, chlorophyll, and turbidity, was examined to gain insights into the Fe dynamics in the bay. The Fe, nitrate-nitrogen and nitrite-nitrogen (NO2 –N + NO3 –N), and phosphate (PO4 –P) concentrations were monitored from June 2011 to July 2013. The results showed that the Fe concentrations before and after March 2012 follow different patterns, and the Fe concentrations in surface seawater 1 year after the tsunami reflected the influence of freshwater inputs. Various forms of Fe, N, and P were monitored after March 2014. Total Fe was significantly correlated with precipitation (represented by an index) and salinity, especially at the river mouths. Comparison of the N:P:Fe ratios at all the sites from March 2014 to November 2016 showed that Fe was abundant, and the ratios differed between the surface water and bottom water. The present study indicates that Fe in Kesennuma Bay is influenced by factors such as the balance between freshwater inputs and ocean water, and the water depth. Further, freshwater from terrestrial areas was the main influence on the Fe concentrations close to the river mouths. Highlights: Changes in the coastal environment and iron (Fe) concentrations in Kesennuma Bay by the 2011 tsunami were investigated. The Fe concentrations before and after March 2012 were different. Water quality including Fe is influenced by many factors, such as the relationship between the freshwater and ocean water, and the water depth. Freshwater from the terrestrial area strongly affects the Fe concentrations in surface seawater in the coastal areas close to the river mouths.